PEMANFAATAN SISTEM INFORMASI GEOGRAFI UNTUK PEMETAAN DAERAH RAWAN KECELAKAN LALU LINTAS (STUDI KASUS: SPGDT KABUPATEN BANTUL) - yuspita sari, Rizky (Jurnal Dialektika Politik, 2024)
Traffic accidents are a common problem for cities. Accidents can occur in different locations at different times and with different causes. Therefore, it is important to determine accident-prone areas in each region. The purpose of this research is to map accident-prone areas and identify the causes of accidents in Bantul Regency. This research uses a quantitative descriptive approach by utilizing geographic information system analysis. The data used in this study used traffic accident reports from Bantul Regency. SPGDT Bantul Regency, journals, reports, online sources, and other relevant documents. The conclusion of this study is that the most accident-prone areas are in Bantul sub-district, the pattern of accident cases forms a cluster, and the causes of accidents are due to road conditions and human error. Therefore, it is important to collaborate with multi-stakeholders in prevention.